A preliminary investigation of domestic squalor in people with a history of alcohol misuse: neuropsychological profile and hoarding behavior – an opportunistic observational study. (16th June 2015) - Gleason, Andrew; Lewis, Matthew; Lee, Sook Meng; Macfarlane, Stephen
ABSTRACT: Background: Domestic squalor has been associated with alcohol misuse but little work has explored this. Executive dysfunction is commonly observed in squalor and is also associated with alcohol misuse. Hoarding can accompany squalor, but it is unclear whether hoarding is also linked with alcohol misuse. This study compared neuropsychology and hoarding status of individuals living in squalor with and without a history of alcohol misuse. Methods: A subgroup analysis was conducted on a series of 69 neuropsychological reports of people living in squalor. Data on cognitive profiles, basic demographics, alcohol use, and hoarding were extracted and analyzed. Results: Alcohol misuse was reported in 25 of the 69 participants (36%). Alcohol misusers were significantly younger (mean age 66.2 years, SD = 10.7) than non-misusers (mean age 75.6 years, SD = 10.3) ( p < 0.00) and significantly more likely to be male ( p = 0.01). No significant differences between the two subgroups were found for estimated premorbid intellectual functioning, Mini Mental State Examination (MMSE) scores, or individual neuropsychological domains. Alcohol misusers were more likely to be living in squalor without hoarding than squalor with hoarding ( p = 0.01). Conclusions: Alcohol misusers living in squalor were less likely to hoard than non-misusers. This finding suggests that alcohol misuse may be a risk factor for squalor via failure to maintain one's environment rather than through intentional accumulation of objects. The similar cognitive profile among those with and without a history of alcohol misuse could represent a common pattern of executive dysfunction that predisposes individuals to squalor regardless of underlying alcohol misuse diagnosis.